Biased emotional attention in patients with dental phobia. (21st December 2018) - Alexopoulos, Johanna; Steinberg, Christian; Liebergesell‐Kilian, Nora Ellen; Hoeffkes, Berit; Doering, Stephan; Junghöfer, Markus
Abstract: Biased motivated attention towards phobia‐relevant pictures is a typical finding in specific phobia. In the visual system, the allocation of motivated attention is indexed by two event‐related potential components – the Early Posterior Negativity and the Late Positive Potential. Enhanced Early Posterior Negativity and Late Positive Potential amplitudes are reliably observed in specific phobia such as, for instance, snake, spider, or blood‐injection‐injury phobia and to some extent also in dental phobia. However, regarding dental phobia results are sparse and its theoretical concept is not undisputed. To further elucidate the electrophysiological characteristics of dental phobia, we investigated visual emotional processing in dental phobia patients and controls. Subjects viewed neutral, phobia‐irrelevant and phobia‐relevant pictures while magnetoencephalographic and behavioural measures were recorded. All patients reported a history of traumatic experiences and depressive and anxiety symptoms, as well as dissociative and posttraumatic symptoms. In the magnetoencephalography, patients showed generally less evoked neural activation at parietal and temporal regions and a reduced differentiation between picture categories compared to controls. At the behavioural level, patients rated phobia‐relevant pictures as clearly more negative as did controls. In contrast to previous reports, our results suggest that dental phobia cannot be associated with the typical effects of biased motivated attention seen in other specific phobias. Instead, results indicate that dental phobia shares typical characteristics with mild forms of posttraumatic stress disorder. Abstract : Biased motivated attention towards phobia‐relevant pictures is a typical finding in specific phobia. In contrast to previous reports, we found reduced evoked neural activation at parietal and temporal regions suggesting that dental phobia cannot be associated with the typical effects of biased motivated attention seen in other specific phobias. Instead, the general hypoactivation indicates that dental phobia shares typical characteristics with mild forms of posttraumatic stress disorder.